(untitled) (Plant Tissue Culture and Biotechnology, 2021)
A study was conducted to standardize a protocol for in-vitro direct regeneration and mass multiplication of Citrus indica Tanaka using shoot tip explants excised from mature trees. Shoot tips were inoculated in MS medium supplemented with varying concentrations and combinations of cytokinins and auxins. MS media when fortified with BAP 0.5 mg/l and 0.5 mg/l BAP + 1.0 mg/l Kn were found to be the best treatments for shoot initiation while MS supplemented with 1 mg/l IBA; 0.5 mg/l NAA + 0.5 mg/l IBA and 0.5 mg/l NAA + 0.5 mg/l IAA were the best treatments for root induction. Among the different media used for hardening, 100 % survivability was obtained when plantlets were hardened using vermicompost as the potting medium. Subsequently, these plantlets were transferred to larger pots and acclimatization was achieved gradually in outdoor conditions. Plant Tissue Cult. & Biotech. 31(1): 13-23, 2021 (June)